Quality Of Service (QOS) Improvement Using Traffic Shaping In ADTEC Batu Pahat - Mohd Yunus, Siti Rodhiah (UTeM, 2016)
QoS is a requirement for ensuring the implementation of specific standard performance to avoid delays in reaching destinations and decreases number of lost packets. Also the performance of the network can be optimized indirectly. Therefore, to ensure network performance, there are a variety of QoS methods and mechanisms to manage and control packet from lost or delayed and also improve network performance. As a Cisco Networking Academy, Department of Computer and Networking has applied a range of delivery methods to provide the relevant and most effective training solution for students. However, all of these methods can quickly consume bandwidth and make the LAN network is poor or totally down for other classes. This project objective is implement traffic shaping mechanism and analyze the impact of generic traffic shaping and class-based traffic shaping on the network. We separated our experiment into three primary cases. In the first case we investigate the fixed bandwidth of 4 Mbps with no QoS applied. Second case we implement the Generic Traffic Shaping mechanism on outbound interface with three different of mean rate and burst size values. The third case, we configured the sub interface of the router that been classed with different VLANs on the network. The conclusion is that the Class based shaping can lead more efficient and give a good quality of network performance. This is because the class based shaping offered more specific traffic management such as classes the users based on the usage and application used. As from the output the average outgoing packet for sub interface in Traffic Shaping router is 99.93% which indicated a good quality in performance.